Pengetahuan Ibu Hamil tentang Psikologi Trimester I di Klinik Sampali Medan Tembung Kota Medan Tahun 2023 - Anike Lisberianti Sihomhombing; Retno Wahyuni; Kismiasih Adethia; Lisa Putri Utami Damanik; Emiya Agustina Surbakti; Grace Adelia Putri (An-Najat, 2023)
Pregnancy is a natural process experienced by women during their reproductive period. During pregnancy, various changes occur both physically and psychologically. Physically, common changes include not menstruating, breast enlargement, changes in the shape of the uterus, weight gain, and changes in the body's organ systems. In addition, pregnant women also experience increased sensory sensitivity, weakened relaxation of the digestive tract muscles, and enlargement of the hands and feet (Zamriati, 2013). Meanwhile, from a psychological aspect, pregnant women tend to be more sensitive, easily anxious, require more attention, and often experience mood swings. They are also more open to themselves and like to share experiences. During pregnancy, mothers often reflect on various things, such as life, happiness, to fear of failure or death (Rahmawati, 2017). In the first trimester, unstable hormonal changes often cause fluctuating emotions, even at risk of depression. Although this anxiety is normal, pregnant women should be able to manage their feelings so that they do not drag on (Indiarti, 2013). Based on this, this study will discuss the relationship between pregnant women's knowledge of psychological changes in the first trimester and their attitudes in dealing with pregnancy at the Sampali Clinic, Medan Tembung District, Medan City, in 2023.